Partial ablation of endometrial glands in dogs after exposure to progestin during the neonatal period - Teixeira, Natalia Soares; Martins, Bianca Barcelos; Volpato, Rodrigo [UNESP]; Gualberto Ramos, Jose Leonardo; Coletto Freitas, Patricia Maria; Laufer-Amorim, Renee [UNESP]; Lopes, Maria Denise [UNESP]; Luz, Marcelo Rezende (Brazilian Coll Animal Reproduction, 2018)
Bitches with uteri devoid of endometrial glands should be sterile, and consequently could contribute to the population control of dogs. Considering that an inadequate exposure of the female reproductive system to steroids can lead to the formation of the uterine gland knock-out (UGKO) phenotype in some species, the aim of this study was to evaluate the effect of serial applications of medroxyprogesterone acetate (MPA) from birth until the age of six months on the development of endometrial glands in bitches. For this purpose, 16 female mongrel dogs from different litters were distributed into either an MPA group (n = 8), animals treated with 10 mg kg sc (Promone-E (R), Pfizer, Brasil) at 3-week intervals, from day one after birth until the age of six months, or a control group (n = 8), composed of animals that only received a 0.9% NaCl solution in place of MPA. At six months of age, ovariohysterectomy was performed and uterine horn samples were collected for histological and immunohistochemical examinations. The bitches from the MPA-treated group presented a 35% decrease in the number of endometrial glands, a larger diameter of the endometrial glands, a greater epithelial height, as well as a greater thickness of the uterine wall, endometrium, and myometrium. However, no significant differences were observed between the two groups in the expression of ER-alpha, ER-beta, and PR on the surface epithelium and endometrial stroma. Therefore, the serial application of MPA from birth until the age of 6 months do not completely ablate the development of the endometrial glands in bitches, but impair it by 35%.
Keywords: ablation; bitch; endometrial glands; receptors; uterus